Adventure Tourism in Nepal Himalayas: Environmental Effects - Genç, Ruhet (Journal of Tourism & Adventure, 2021)
Nepal is known as an ideal destination for adventure tourism with its diverse natural attractions and cultural heritage. However, The Nepali Himalayas is highly vulnerable to human influenced change, occurring at local and national scales. The objective of this manuscript is to assess the overall situation of the adventure tourism activities in the Nepali Himalayas and various environmental effects related to it. The methodology will be literature review with an evaluation of the findings. The collected data from publications of the Nepal Ministry of Culture, Tourism and Civil Aviation is organized and analyzed in a descriptive way where some of the data were presented in tabular form using a simple statistical tool. At the end, the manuscript will suggest the establishment of educational programs focused on different target groups and essential policy measures for local stakeholders and governmental bodies to reduce adverse environmental impacts of adventure travels.